Spatio-temporal variations of vegetation cover and its influencing factors in highland lake basin - Liu, Zhoujiang; Hu, Wenxian; Ma, Liming; Huang, Xiaoxia (Frontiers in Environmental Science, 2024)
Exploring dynamic vegetation changes and identifying the factors driving these changes are important for evaluating global ecosystem processes. Based on the pixel binary model, coefficient of variation, Theil-Sen median trend analysis, geographic detector, and Pearson correlation coefficient, this study analyzed vegetation cover variations and the factors influencing these changes in the Erhai Lake Basin, one of the most important plateau lakes in China. Vegetation cover exhibited a continuously increasing trend, with the proportion of high vegetation coverage consistently ranking first. Land cover is an effective explanatory factor for vegetation cover, and FVC shows obvious variation rules associated with elevation, land cover, population, and landform. It is important to highlight that the combination of two factors influences vegetation dynamics more significantly than one factor alone, with the interaction between land cover type and nightlight illumination being more powerful. These results enhance our understanding of the complex processes of vegetation cover variation in plateau lake catchments and offer a scientific reference for improving the spatial layout of vegetation in fragile ecosystems.